Integrating Human Resource Management into Lean: Its Implementation and Benefits - Dr. Karun Mehta (Innovative Research Thoughts, 2023)
Lean management or lean thinking is a process improvement technique that along with Six Sigma is used in an increasing range of workplaces. This special issue focuses on the use of Lean in developed countries. This increased usage reflects a growing propensity for managers to launch initiatives to upgrade the efficiency and productivity of the enterprises that they manage, usually in an attempt to enhance the cost-effectiveness of operations. HR departments are under increasing pressure to ensure business success through effective HR practices. Lean HR can help organizations improve processes, leading to increased productivity and better performance. A major challenge for all organizations is to improve efficiency and to ensure continuous improvement. For the HR department this is a double challenge as the HR department itself should meet the requirements of the organizations it serves in an efficient way, and the HR department should be an active partner in promoting and training improvement actions in relation to the main tasks of the organization. Lean implies a bottom-up approach; it requires empowerment and involvement of all employees and a new type of leadership. This paper will discuss some experiences gained so far and present some potentials of this approach. One concrete result has for instance been the redesign of management of course planning in order to ensure better response to new needs, more efficient use of training resources and more robust management of courses